Effects Of Empty Fruit Bunch Compost And Arbuscular Mycorrhiza On Nutrient Uptake And Growth Of Grain Maize - Md Jaafar, Noraini (2007)

(untitled)
The current interest in reducing the application of chemical fertilizer and increasing demand for combined effects of beneficial fungi and organic compost can have great impact on crop production and sustainable agriculture. Laboratory and glasshouse experiments were conducted to determine the effects of different rates of empty fruit bunch (EFB) compost and arbuscular mycorrhizal (AM) activity on plant growth, nutrient uptake, soil chemical and microbiological properties. An incubation experiment was conducted under laboratory condition to determine the effects of different rate of empty fruit bunch compost (EFBC) on nutrient release, changes in soil chemical properties and microbial population. Unsterilized Serdang series soil was amended with 0, 2.5 and 7.5% EFBC and soil was sampled at 3, 7, 14, 28, 56 and 84 day. Results showed that increasing rate of EFBC had significantly (P<0.05) improved the soil chemical properties in which higher soil pH, total N, ammonium-N and nitrate-N, soil available P, C, K, Ca and Mg was found in soil amended with 7.5% EFBC. Higher rate of EFB significantly (P<0.05) resulted in higher populations of soil fungi, bacteria and actinomycetes. This study indicated that addition of EFBC to soil may be an alternative method in improving the nutrients availability in highly weathered soils such as Serdang series soil. Applying EFBC as organic amendment in highly weathered soils, however, may require addition of effective or beneficial microorganisms such as AM to fully benefit the soil. A glasshouse experiment was then conducted to assess the effects of combined application of EFBC and AM on the performance of AM in improving growth of grain maize and soil properties. Soil was treated with 3 rates of EFBC (0, 2.5 and 7.5% EFBC) with and without AM. Plants and soil were sampled at 7, 14, 28 and 56 days after planting (DAP) and analyzed for plant growth, nutrient uptake, soil chemical and microbiological properties. Growth of grain maize was significantly (P<0.05) affected by EFBC and AM application. Plants inoculated with AM were able to absorb more nutrients released from EFBC than the nonmycorrhizal plants. Mycorrhizal plants also showed lower requirement of EFBC than nonmycorrhizal plants. Application of 2.5% EFBC with AM gave better (P<0.05) shoot maize biomass and root biomass than nonmycorrhizal plants. After 56 DAP, AM inoculation increase in maize plant biomass by 60% compared to plants without AM. Inoculation with AM and application of EFBC also increased the uptake of N, P, K, Ca and Mg by maize. Application of EFBC stimulated AM development throughout 56 DAP. There was 60% spore production in soils with EFBC than the control soil. Application of EFBC also improved soil nutrients and enhanced microbial activities which may induce the mycorrhizal symbiosis with plant roots. This can be observed in increasing mycorrhizal spore production with increasing EFBC rate. However, the highest root infections in 7.5% EFBC+M was observed to be insignificantly (P>0.05) different to that in 2.5% EFBC+M and did not result in the highest plant growth. Lower rate of EFBC (2.5% EFBC) having intermediate values of AM spores production (300 spores 10 g soil-1) and percentage of infection (69.68%) promoted highest plant growth at 56 DAP. Application of 2.5% EFBC was sufficient for mycorrhizal plants to attain the highest growth compared to the highest EFBC application rate of 7.5% EFBC required by nonmycorrhizal plants. The results suggest that lower compost rate was sufficient to stimulate plant growth when AM is being inoculated into soil. Inoculation of beneficial AM helps to reduce the optimum rate of compost application and the production cost. The study also showed that combined application of AM and EFBC have the potential to be applied for improved maize production in highly weathered soil.